2023
DOI: 10.1021/acs.chemmater.2c03723
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Oxygen Vacancies in IrOx Clusters Supported on Metal–Organic Framework Derived Porous CeO2 for Enhanced Oxygen Evolution in Acidic Media

Abstract: Developing highly active and stable electrocatalysts for the oxygen evolution reaction (OER) in acidic media for proton exchange membrane water electrolysis is urgent but still challenging. Herein, porous CeO2-supported IrO x clusters with different oxygen vacancy (Ov) concentrations are synthesized by the aid of N-rich and N-free isostructural Ce-based metal–organic frameworks (Ce-MOFs) as templates. Ov concentration in the derived IrO x clusters is effectively regulated by the presence of heteroatoms in MO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Recently, Li et al further developed porous CeO 2 ‐supported IrO x with high V O which exhibited an excellent acidic OER performance (251 mV at 10 mA cm −2 for 90 h) (Figure 10D). 135 By modifying the CeO 2 support, the authors maximized the ECSA as indirectly confirmed by electrochemical double‐layer capacitance comparison ( C dl ) (Figure 10E).…”
Section: Improving Acidic Oer Activitymentioning
confidence: 79%
See 1 more Smart Citation
“…Recently, Li et al further developed porous CeO 2 ‐supported IrO x with high V O which exhibited an excellent acidic OER performance (251 mV at 10 mA cm −2 for 90 h) (Figure 10D). 135 By modifying the CeO 2 support, the authors maximized the ECSA as indirectly confirmed by electrochemical double‐layer capacitance comparison ( C dl ) (Figure 10E).…”
Section: Improving Acidic Oer Activitymentioning
confidence: 79%
“…(E) Comparison of calculated C dl values of supported and nonsupported IrO 2 . Reproduced with permission 135 . Copyright 2023 American Chemical Society.…”
Section: Improving Acidic Oer Activitymentioning
confidence: 99%
“…Since Ta 2 O 5 was fully covered by IrRuO x and underwent air treatment, the remaining oxygen vacancies also originated from IrRuO x clusters due to their high surface-to-volume ratios. 35…”
Section: Resultsmentioning
confidence: 99%
“…Since Ta 2 O 5 was fully covered by IrRuO x and underwent air treatment, the remaining oxygen vacancies also originated from IrRuO x clusters due to their high surface-to-volume ratios. 35 The surface compositions of the studied samples were examined by XPS, and Ta, Ir, Ru, and O were all detected in the full spectrum of IrRuO x /Ta 2 O 5 (Fig. 3D).…”
Section: Physical Characterization Of the Catalystsmentioning
confidence: 99%
“…The O 1s spectrum of IrO 2 -300 °C in Figure 9a consists of three contributions at 529.9, 531.7 and 533.2 eV, which are attributed to lattice oxygen (O), Ir-OH (possibly formed at vacancy sites) and absorbed water (H 2 O), respectively. [82][83] The contents of each of these components is listed in Table S3. The most significant change is that the Ir-OH percentage in the sample decreased after annealing the sample from RT to 300 °C.…”
Section: Resultsmentioning
confidence: 99%